(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service was carried out to address three main challenges in history education: the limited optimization of teacher competence, the lack of variety and innovation in learning media, and the need for better accessibility to information. To respond to these issues, a training program was organized on the use of Android-based learning media with Smart Apps Creator (SAC), integrated with differentiated learning, as an effort to support the implementation of the independent curriculum and enhance the competence of high school history teachers in Tasikmalaya Regency. The purpose of this activity was to improve teachers’ competence in designing and applying innovative learning media that can support more interactive and effective history learning. The participants consisted of 23 history teachers, and the instruments used were questionnaires (pretest and posttest)to measure competence levels. The method included four stages: (1) providing instruments before training, (2) delivering modules, (3) conducting hands-on training sessions, and (4) administering instruments after training. The results showed a significant improvement in teacher competence, with the average score increasing by 23%, from 70in the pretest to 93 in the posttest. Furthermore, after the training, participants successfully applied Smart Apps Creator in their classrooms to design and implement interactive history learning activities. In conclusion, this program effectively enhanced teacher competence and encouraged the integration of digital media in classroom practice, thereby contributing to improved quality of history education.